Enhancing Productivity and Profitability of Tribal Farmers of Jharkhand through Institutional Linkages - B. K. Singh , Ambrish Kumar Sharma , Nishi Sharma , R. P. Singh Ratan , Valaria Lakra and Kishan Singh (Indian Journal of Extension Education, 2016)
Public sector extension continues to be the most important source of information for majority of farmers but itsperformance is under scrutiny for quite some time and questions are being raised on its capability to deliver goods andservices in the rapidly changing environment. The shifting emphasis of Indian agriculture towards diversification,commercialization, sustainability and efficiency has made it necessary to look for new approaches and models forextension. The Indian Agricultural Research Institute (IARI) over the period has experimented with different extensionapproaches and models which have immensely contributed to the development of roadmaps for national extensionsystems. One such model of Institutional partnership based extension to diffuse IARI technologies all over India, apartnership led extension was initiated under National Extension Programme. Under this programme the IARI varietiesand production technologies were diffused in collaboration with 15 ICAR Institutes and SAUs for quick and wider spreadto a large number of farmers in different parts of the country. One such collaboration with Birsa Agricultural University(BAU), Ranchi was initiated to address the production problem of tribal farmers of Jharkhand during year 2007-08 (RabiSeason). The specific objectives of the project are to demonstrate improved seeds of major crops and to produce qualityseed by the farmers themselves. Although, agriculture is main source of livelihood for 80 per cent of the population inJharkhand, it is characterized by reliance on low investment, low productivity and mono cropping with paddy as theoverriding crop. Under this collaboration suitable crop varieties of paddy, wheat, mustard, lentil and vegetables weredemonstrated on farmers' fields. Farmers were continuously giving their opinion towards selected traits of thedemonstrated improved varieties of rice. Paddy variety Pusa 2511 was preferred by the farmers due to its high yield,aroma and long grain quality. It has been accepted and adopted by the farmers in the demonstration villages as well asnearby villages. Rice variety Jaldi Dhan-13 was demonstrated during kharif 2012 and 2013 was liked owing to its coarsegrains for their own consumption as they perform hard physical activities and found this variety suitable for their uplandareas. Among rabi crops, wheat variety HD-2733 was liked by farmers due to its high yield, varieties HD-2985 and HD2932 due to their relatively early maturing trait. Pusa Jaikisan variety of mustard was preferred by the farmers due to itshigh yield and relatively more oil content. Majority of the farmers preferred to grow mustard with wheat, due to the factthat area under irrigation was relatively less. The farmers also revealed that varieties provided by IARI were insect-pestand disease resistant. The paper describes the process and outcome of the IARI interventions for having its implicationsamong extension professionals and practitioners in India.